Respiratory Infections during SARS Outbreak, Hong Kong, 2003 - Janice Y.C. Lo; Thomas Tsang; Yiu-hong Leung; Eugene Y. H. Yeung; Thomson Wu; Wilina Lim (2005)
Abstract The effect of community hygienic measures during the outbreak of severe acute respiratory syndrome in Hong Kong was studied by comparing the proportion of positive specimens of various respiratory viruses in 2003 with those from 1998 to 2002. Community hygienic measures significantly reduced the incidence of various respiratory viral infections.